Exploring the sense of place of traditional shopping streets through Instagram's visual images and narratives - Kusumowidagdo, Astrid; Ujang, Norsidah; Rahadiyanti, Melania; Ramli, Nurul Atikah (Emerald Publishing, 2022)
Purpose: This study aims to capture a sense of place by analysing the physical attributes of the traditional shopping streets located in Indonesia and Malaysia through Instagram posts. Design/methodology/approach: This study adopted a direct content analysis using visual images of 400 posts of Indonesian and Malaysian respondents. The Instagram Application Programming Interface (API) was used to extract data from Instagram posts. It is then followed by the quantitative analysis to determine the frequencies of visual and narrative representations of physical attributes defining the sense of place. Findings: Five visual and narrative categories, namely architectural style, store design, special focal points, and the varieties of products and services that represent the physical attributes of shopping streets, were investigated. The findings would benefit the urban preservation initiatives so that the sense of place as authentic tourism destinations can be secured. Social implications: The awareness of the traditional shopping street as a place of character, especially from social media users, is able to create local values that lead to place imageability and promote national tourism. Originality/value: This study captured the sense of traditional places based on the people’s identifications that were shared on social media platforms. The posts’ preferences confirmed the significance of traditional shopping streets as a place of attraction and identity. The findings addressed the functions of physical attributes in sustaining the historical and authentic values of traditional shopping streets.